Criminal justice - Sharma, Devendra Kumar (New Delhi Random Publications, 2019)
The purpose of this book is to provide challenging and practical advice to the general public and government officials to stand against the venerable activities of criminals which result in crucial offences and losses to human community.
Keywords: Criminal justice; Administration of Criminal procedure